2018
DOI: 10.5435/jaaos-d-16-00547
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality in Patients With Rotator Cuff Disease

Abstract: Objectives: Sleep disturbance may be an important prognostic variable driving patients to seek treatment for rotator cuff disease related shoulder pain. Currently, little is known on the influence of rotator cuff pathology on sleep. The purpose of this study was to determine which patient factors correlate with sleep disturbance in patients with atraumatic rotator cuff disease. Methods: A prospective, nonrandomized single surgeon cross-sectional cohort study was performed evaluating the effects of rotator cuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 21 publications
4
55
0
Order By: Relevance
“…Cross-sectional studies investigated the quality of sleep in other musculoskeletal diseases such as osteoarthritis of the knee, and rotator cuff tear 21 , 22 , and recent prospective case-series measured their changes after surgical treatment 23 , 24 . In such joint diseases, pain is generally reduced during sleep, because the gravitational joint force is decreased in the lying position.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies investigated the quality of sleep in other musculoskeletal diseases such as osteoarthritis of the knee, and rotator cuff tear 21 , 22 , and recent prospective case-series measured their changes after surgical treatment 23 , 24 . In such joint diseases, pain is generally reduced during sleep, because the gravitational joint force is decreased in the lying position.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, sleep disorders are among the most frequent complaints of patients with RC tears. Recent studies highlighted the impact that other human variables, such as sleep quality, patient expectation, cognitive, affective psychologic factors or distress, and socioeconomic status may have on the clinical results of RC tears [13,[43][44][45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that sleep disorders involve 15% to 35% of the general population [1,2]. Sleep disorder is a medical disorder of the sleep patterns that may be serious enough to interfere with normal physical, mental, social, and emotional functioning and it negatively affects patient’s quality of life, causing mood disorders and anxiety [3,4]. Sleep a few hours at night can have consequences on emotional condition [3,5] and on the ability to perform daily life activities [6].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disturbance is one of the most common complains of patients with RC disease [1,3], with only 11% of patients with symptomatic RC tears claiming to have a normal sleep [1,14]. Patients with RC tears seems to have more sleep disturbances compared with patients with other shoulder disorders like RC tendinopathies [3], or subacromial impingement [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation